Fatty acid profiles from twenty-one plant species identified as palatable for pasture-raised laying hens - Gonzalo J. Diaz; Yandy J. Aguillón-Páez (PLoS ONE, 2025)
A study was conducted to determine the fatty acid (FA) profiles of 21 plants voluntarily eaten by pasture-raised hens. Samples were collected from a very humid premontane forest during two dry and two rainy seasons within a year. FA were analyzed as methyl esters using a gas chromatograph coupled with a flame ionization detector. In general, no major changes in total saturated (SFAs), monounsaturated (MUFAs) or polyunsaturated FA (PUFAs) were observed within each plant among the four sampling times. However, for seven plants, large differences (3 times as much) in MUFAs content were observed and for Heliconia sp . the PUFAs content in the January sampling was almost double than the one found in July (43.3 vs 22.2%). On the other hand, large interspecies differences were observed in FA composition; for instance, Bidens rubifolia was predominantly PUFA-rich while Musa paradisiaca and Heliconia sp . were predominantly SFA-rich. The predominant FA in 86% of the plants were the PUFAs ɑ-linolenic acid (ALA, omega-3) and linoleic acid (LA, omega-6), and in almost all plants, the omega-6 content was lower than the omega-3 content. Therefore, the omega-6 to omega-3 FA ratio in all plants ranged from 0.1 to 1.1, which is an ideal ratio to improve the n-6/n-3 ratio of egg yolks. Interestingly, maize leaves were found to contain a high percentage of ALA and n-6/n-3 ratios ranging from 0.1 to 0.2 and could therefore be considered in pasture-raised laying hens. The results of the present study indicate that grazing plants can be a sustainable alternative source of n-3 FA for laying hens, in replacement of expensive marine sources.